Manfaat Ekonomi Kelangsungan Ekosistem Terumbu Karang di Perairan Pulau Enggano Provisi Bengkulu: Sebuah Telaah Pustaka - Siregar, Sri Haniarti; Oktaviani, Sefri; Fauzi, Rizki; Reflis, Reflis; Satria P. Utama (Yayasan Literasi Sains Indonesia, 2023)
Enggano Island has several potential biological resources that can improve the economy in the area, one of which is coral reefs. The biological resource potential of coral reef ecosystems in the Enggano Island area is one of the mainstays of community livelihoods, namely as a fishing ground for fishermen. This activity has been carried out for a long time and the intensity is getting higher from time to time, so it is necessary to conduct a study to calculate the value of the economic benefits of coral reef ecosystems in the Enggano Island area in the form of direct and indirect economic value for the benefit of sustainable management and utilisation. This literature review aims to provide information to various parties related to the Economic Benefits of Coral Reef Ecosystem Sustainability in Enggano Island Waters, Bengkulu Province. The results of the review of previous studies showed that the value of direct economic benefits amounted to Rp. 561,327,640, indirect benefits amounted to Rp. 46,342,500,000, optional benefits amounted to Rp. 2,516,077,983, and the benefits of the existence of the Enggano Island coral reef ecosystem amounted to Rp. 127,425,000,000. All of these economic benefits have been felt by fishing communities and other user communities.